Creating and Development of The Rubber Latex Uterine Contraction Practice Model Using Water Pressure Control Mechanism for Nursing Students - Siriwallop, Rattanapenporn; Phalasri, Amornrat; Udomariyasap, Pongputhai; Wiwattanasirikul, Rungtawan (Journal of health and health management, 2022)
The objective of this research and development is to create and develop the rubber latex uterine contraction practice model using a water pressure control mechanism. To compare uterine contraction assessment skills by the rubber latex uterine contraction practice model using a water pressure control mechanism for nursing students before and after the experiment. Moreover, to study their satisfaction with the rubber latex uterine contraction practice model using water pressure. This research consists of 3 phases. The participants include 50 second-year nursing students, from the Faculty of Nursing, Chaiyaphum Rajabhat University. The research instruments are the rubber latex uterine contraction practice model using a water pressure control mechanism, a satisfaction assessment form, and a satisfaction assessment form. The reliability was 0.87. The reliability coefficient of the uterine contraction skill assessment form and the satisfaction assessment form were 0.88 and 0.76. Data were analyzed using content analysis descriptive statistics and t-test (pair t–test). The results revealed that the half-body pregnant woman’s model is made of fiberglass covered with rubber, a large abdominal wall, and inside a basin containing a bag to control water pressure. Outwardly appearance resembles a human. This model can be used to measure the uterine contraction assessment. The average scores of the uterine contraction assessment skills after using this model were significantly higher than before the experiment (p-value < 0.05). The overall satisfaction with the uterine contraction measurement skills training with this model for nursing students was at a high level ( =4.33, S.D.=0.58). Therefore, the rubber latex uterine contraction practice model using a water pressure control mechanism can be mimic uterine contractions and suitable for teaching in Maternity Nursing and Midwifery subjects.